PENGARUH MEDIA PEMBELAJARAN BERBASIS DIGITAL TERHADAP MINAT BELAJAR SISWA DI MI AL-KIFAYAH PEKANBARU - Ahmad Romadon; MHMD Habibi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital technology has driven significant changes in learning practices in elementary schools, including Islamic elementary schools (madrasah ibtidaiyah). Digital-based learning media is seen as an innovation with the potential to increase student learning interest through interactive, visual, and contextual presentation of materials. This study aims to analyze the influence of digital-based learning media on student learning interest at MI Al-Kifayah Pekanbaru. This study used a quantitative approach with a survey method. The sample consisted of fourth and fifth grade students selected using a purposive sampling technique. Data were collected through a learning interest questionnaire and a digital learning media usage questionnaire, which were tested for validity and reliability. Data analysis was conducted using a simple linear regression test with statistical software. The results showed that digital-based learning media had a positive and significant effect on student learning interest. This finding suggests that the more optimal the use of digital learning media, the higher the students' learning interest. This research is expected to provide practical contributions for teachers and schools in developing effective digital-based learning strategies that are appropriate to the characteristics of Islamic elementary school students.